2018
DOI: 10.1111/ggr.12236
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Isotope Ratios of Standard Solutions and Geological Reference Materials Measured by MCICPMS

Abstract: We report high‐precision cadmium isotope ratios for a series of standard solutions and geological reference materials for interlaboratory comparison. Complete separation of Cd from a matrix in geological samples was achieved using AG MP‐1M anion exchange resin with > 97.8% recovery. Cadmium isotope ratios were measured by both Neptune plus multi‐collector‐inductively coupled plasma‐mass spectrometry (MC‐ICP‐MS) and Nu Plasma II MC‐ICP‐MS at low‐resolution mode. Both sample calibrator bracketing (SSB) and doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 58 publications
11
40
1
Order By: Relevance
“…The Cd mass fractions of soil reference materials were reported by NIST and IGGE, and most of the values for rock reference materials were determined by isotope dilution mass spectrometry in this study. With the exception of GSS‐1 and NOD‐P‐1, only minimal Cd isotope data for NIST SRM 2709, 2709a, 2711, 2711a, BIR‐1, and AGV‐2 have been reported (Cloquet et al , Pallavicini et al , Wiggenhauser et al , Palk et al , Imseng et al , Li et al ), and the Cd isotope values of some of the reference materials are reported for the first time in this study.…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…The Cd mass fractions of soil reference materials were reported by NIST and IGGE, and most of the values for rock reference materials were determined by isotope dilution mass spectrometry in this study. With the exception of GSS‐1 and NOD‐P‐1, only minimal Cd isotope data for NIST SRM 2709, 2709a, 2711, 2711a, BIR‐1, and AGV‐2 have been reported (Cloquet et al , Pallavicini et al , Wiggenhauser et al , Palk et al , Imseng et al , Li et al ), and the Cd isotope values of some of the reference materials are reported for the first time in this study.…”
Section: Resultsmentioning
confidence: 61%
“…, Li et al . ); other symbols represent the data from this study. Errors of data from the literature and this study reflect two standard deviations (2 s ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations